Implementation Of Big Data In Quality Assurance Of Accounting Department At SMKN 1 Randudongkal - Slamet Fauzan; Cipto Wardoyo; Fery Dwi Candra; Khilmatul Mauludah; Kurniawan (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
The importance of quality assurance in improving school performance. The Education Unit Accreditation Instrument is a reference in the assessment of quality assurance. background of the problem, research objectives, methods used, research results. Vocational high schools still do not use the indicators on the instrument as a reference for quality assurance. The purpose of this study is to explore the completeness and feasibility of quality assurance standards at SMKN 1 Randudongkal which will be used as a basis for consideration in preparing the accreditation assessment. This research uses a case study approach. The sample in this study was determined using the purposive sampling method. The results of this study are the quality of graduates, the learning process, teachers, and school management as a source of indicators for achieving school quality. To improve the quality, schools use big data in planning, evaluation and school follow-up plans. The role of Big Data in school quality assurance is to collect all data to facilitate school quality assurance parties in assessing school performance based on four points that must be achieved in quality assurance, namely Quality of Graduates, Learning Processes, Quality of Teachers, and School Management. However, the main things that need to be developed in the graduate quality assurance process based on IASP 2020 include the need for a correct understanding of the instrument, teamwork, and the need to carry out management functions supported by leadership abilities that match the characteristics of each school.